The Cases of Criminality and Law Violations among Young People and Minors - HUSEYNOVA, Leyla; ALIYEVA, Mehriban; GOJAEVA, Elmira; AHMADOVA, Esmira (Journal of Research in Educational Sciences; Vol 15 No 2 (2024): JRES Volume XV, Issue 2(18), Winter 2024DO - 10.14505/jres.v15.2(18).04, 2024)
The chosen scientific article mainly scrutinizes the cases of criminality and law violations among young people as well as minors, which were characterized as crucial social problems. The study identified the main purpose of the spread of criminal cases among young people and the trend of their growth, as well as factors that actively influence this process. The criminality and delinquency among young people and minors are treated as a cybernetic system, which is justified from the point of view of the systematic approach envisaging a socio-economic system with special complexity, dynamism, emergence, and stochasticity in the paper. Global experience with juvenile offenders sheds light on the complex and varied needs of children in conflict with the law. Much of the growing literature on deviant behavior in juvenile offenders shows significant overlap between criminological, social, and medical research. Based on the econometric approach, multi-regression models of the dependence of criminality among young people on the influencing regressors of the environment were built, their qualitative characteristics were tested and mathematically justified that they are a suitable mechanism for optimal management and forecasting in the paper.